Convergent Validity of the Patient Reported Outcome Measurement Information System-Pediatric Physical Activity Instrument (PROMIS®-PA) with Wearable Devices in Adolescents - Reem A. Algheryafi; Katherine B. Bevans; Shivayogi V. Hiremath; Jin-Shei Lai; Carole A. Tucker (MDPI AG, 2023)
The study was conducted mainly to examine the convergent validity of the Patient Reported Outcome Measurement Information System-Pediatric Physical Activity instrument (PROMIS®®®-PA) with step counts from wearable devices and another validated self-reported outcome measure. As a secondary aim, we explored the effect of different recall time frames (7-day, end-of-day [EoD], and ecological momentary assessment [EMA] time frames during the day) in terms of their feasibility and associations with each other and with step counts. This was a prospective cohort study that examined the associations between measures of PA in school-age children and adolescents (n = 84, aged 10-20). The participants wore Fitbit devices for 7 consecutive days, and then completed the 7-day-recall PROMIS-PA short form and Youth Activity Profile (YAP). Additional analyses were completed in a sub-sample (n = 25, aged 11-18 years) using the PROMIS-PA for the EMA at five intervals during the day (shorter form) and at the EoD. In the total sample, the PROMIS-PA results showed positive moderate correlations with the YAP and average daily steps (r = 0.533, p < 0.001 and r = 0.346, p = 0.002, respectively). In the sub-sample, the 7-day PROMIS-PA was highly correlated with the averaged EMA or EoD ratings for the week, and moderately correlated with the daily step counts. These findings support the validity of the PROMIS-PA as a measure of self-reported physical activity. Adolescents demonstrated higher compliance rates and preference for the 7-day recall and EoD assessments compared to more frequent EMA reporting.